Assessment of 18 endocrine disrupting chemicals in tap water samples from Klang Valley, Malaysia - Haron, Didi Erwandi Mohamad; Yoneda, Minoru; Hod, Rafidah; Ramli, Mohd Redzuan; Aziz, Mohd Yusmaidie (Springer, 2023)
Multiclass of endocrine disrupting chemicals (EDCs) such as nine perfluoroalkyl and polyfluoroalkyl substances (PFAS), five bisphenols, and four parabens were analysed in tap water samples from Malaysia’s Klang Valley region. All samples were analysed using liquid chromatography mass tandem spectrometry (LC–MS/MS) with limit of quantitation (LOQ) ranged between 0.015 and 5 ng/mL. Fifteen of the 18 EDCs were tested positive in tap water samples, with total EDC concentrations ranging from 0.28 to 5516 ng/L for all 61 sampling point locations. In a specific area of the Klang Valley, the total concentration of EDCs was found to be highest in Hulu Langat, followed by Sepang, Putrajaya, Petaling, Kuala Lumpur, Seremban, and Gombak/Klang. PFAS and paraben were the most found EDCs in all tap water samples. Meanwhile, ethyl paraben (EtP) exhibited the highest detection rate, with 90.2% of all locations showing its presence. Over 60% of the regions showed the presence of perfluoro-n-butanoic acid (PFBA), perfluoro-n-hexanoic acid (PFHXA), perfluoro-n-octanoic acid (PFOA), perfluoro-n-nonanoic acid (PFNA), and perfluoro-1-octanesulfonate (PFOS), whereas the frequency of detection for other compounds was less than 40%. The spatial distribution and mean concentrations of EDCs in the Klang Valley regions revealed that Hulu Langat, Petaling Jaya, and Putrajaya exhibited higher levels of bisphenol A (BPA). On the other hand, Kuala Lumpur and Sepang displayed the highest mean concentrations of PFBA. In the worst scenario, the estimated daily intake (EDI) and risk quotient of some EDCs in this study exceeded the acceptable daily limits recommended by international standards, particularly for BPA, PFOA, PFOS, and PFNA, where the risk quotient (RQ) was found to be greater than 1, indicating a high risk to human health. The increasing presence of EDCs in tap water is undoubtedly a cause for concern as these substances can have adverse health consequences. This highlights the necessity for a standardised approach to evaluating EDC exposure and its direct impact on human populations’ health.